2022
DOI: 10.3390/ijms23073434
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Chemokine Receptor CCR1 in Burkitt Lymphoma Cell Lines Is Linked to the CD10-Negative Cell Phenotype and Co-Expression of the EBV Latent Genes EBNA2, LMP1, and LMP2

Abstract: Chemokines and their receptors regulate the migration of immune cells and the dissemination of cancer cells. CCR1, CCR2, CCR3, and CCR5 all belong to a single protein homology cluster and respond to the same inflammatory chemokines. We previously reported that CCR1 and CCR2B are induced upon Epstein-Barr virus (EBV) infection of B cells in vitro. EBV is present in almost all cases of endemic Burkitt lymphoma (BL); however, the contribution of EBV in the pathogenesis of the disease is not fully understood. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…CCR1 is one of the C-C chemokine receptors and has corresponding responses to a variety of inflammatory chemokines. [44] Chua et al [45] found that the expression of CCR1 in macrophages of critically ill COVID-19 patients was significantly increased. CCR1 can induce the recruitment of monocytes into the lung parenchyma by binding to CCL2 or CCL3 in vivo and then differentiating into inflammatory macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…CCR1 is one of the C-C chemokine receptors and has corresponding responses to a variety of inflammatory chemokines. [44] Chua et al [45] found that the expression of CCR1 in macrophages of critically ill COVID-19 patients was significantly increased. CCR1 can induce the recruitment of monocytes into the lung parenchyma by binding to CCL2 or CCL3 in vivo and then differentiating into inflammatory macrophages.…”
Section: Discussionmentioning
confidence: 99%